Perlakuan Akuntansi Atas Asset Tetap Pada CV The 999 Project - Kemas Welly Angga Permana; Yustin Kurniawan; Anton Trianto; Dimas Try Handoko; Masnoni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine the accounting treatment of fixed assets at CV The 999 Project which includes acquisition of fixed assets, calculation of depreciation expense, and disposal of fixed assets. This study uses direct interviews with the company, direct observation of the company and literature studies as a reference. Based on the data obtained (list of fixed assets, profit and loss statements, and statements of financial position of the company for 2018, 2019, 2020 and 2021). As a result of the analysis, the authors found several problems, namely CV The 999 Project was not correct in calculating the acquisition price of fixed assets because it only recorded the value of the purchase price without taking into account other costs associated with these fixed assets. In addition, CV The 999 Project calculates the depreciation expense of fixed assets acquired in the current year for a full year. In this final report the author will analyze the calculation of the acquisition cost, depreciation of fixed assets and disposal of fixed assets and their presentation in the financial statements with SAK EMKM as a benchmark. Based on the results of the analysis, the company should make an appropriate calculation of the acquisition cost, depreciation of fixed assets and retirement of its fixed assets in accordance with the applicable Financial Accounting Standards so that the profit presented in the financial statements can reflect the true value.